La houe et la ruse - Leonardo Pires Rosse (Ateliers d'Anthropologie)
What displacement principles guide farmers when they collectively clear fields? Based on accounts of events during collective clearing sessions in the upper Jequitinhonha valley (south-central Brazil), this article aims to bring out the special grammar of these processes, as well as its simultaneous links to a productive reasoning, to rivalry practices, and to a certain festive experience of work.